Regulatory network features in Listeria monocytogenes—changing the way we talk - Guariglia-Oropeza, Veronica; Orsi, Renato H.; Wiedmann, Martin; Yu, Haiyuan; Boor, Kathryn J.; Guldimann, Claudia (Frontiers in Cellular and Infection Microbiology, 2014)
Our understanding of how pathogens shape their gene expression in response to environmental changes is ever growing. Advances in Bioinformatics have made it possible to model complex systems and integrate data form variable sources into one large regulatory network. In these analyses, regulatory networks are typically broken down into regulatory motifs such as feed-forward loops or auto-regulatory feedbacks, which serves to simplify the structure, while the functional implications of different regulatory motifs allow to make informed assumptions about the function of a specific regulatory pathway. Here we review the basic concepts of network features and use this language to break down the regulatory networks that govern the interactions between the main regulators of stress response, virulence and transmission in Listeria monocytogenes. We point out the advantage that taking a “systems approach” could have for our understanding of gene functions, the detection of distant regulatory inputs, interspecies comparisons, and co-expression.